Three-Dimensional Numerical Simulation of a Rotating Detonation Engine: Effects of the Throat of a Converging-Diverging Nozzle on Engine Performance. Issue 11 (1st December 2016) - Eto, Seiichiro; Tsuboi, Nobuyuki; Takayuki, Kojima; Hayashi, A. Koichi
ABSTRACT: The effect of a converging-diverging nozzle on the performance of a rotating detonation engine was estimated using three-dimensional numerical simulations with a detailed chemical reaction model. The nozzle in this article is composed of a long constant cross section, a short converging section, and a diverging section. The expansion area ratios of nozzles A and B in this article are 2.0 and 1.89, respectively. The periodic exhaust oscillation due to rotating detonation is considerably reduced by nozzle A. The variation of the time-averaged pressure is approximately 0.0048 MPa and the ratio to the time-averaged value is 1.3%. For nozzle B, the variation in pressure is approximately 0.018 MPa, and the ratio to the time-averaged value is 5%. The specific impulse of nozzle A increases by approximately 11 s (3.8%) compared with the value of nozzle B.